(x+3)(x-5)=(x+3)x(x+3)

Simple and best practice solution for (x+3)(x-5)=(x+3)x(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)(x-5)=(x+3)x(x+3) equation:


Simplifying
(x + 3)(x + -5) = (x + 3) * x(x + 3)

Reorder the terms:
(3 + x)(x + -5) = (x + 3) * x(x + 3)

Reorder the terms:
(3 + x)(-5 + x) = (x + 3) * x(x + 3)

Multiply (3 + x) * (-5 + x)
(3(-5 + x) + x(-5 + x)) = (x + 3) * x(x + 3)
((-5 * 3 + x * 3) + x(-5 + x)) = (x + 3) * x(x + 3)
((-15 + 3x) + x(-5 + x)) = (x + 3) * x(x + 3)
(-15 + 3x + (-5 * x + x * x)) = (x + 3) * x(x + 3)
(-15 + 3x + (-5x + x2)) = (x + 3) * x(x + 3)

Combine like terms: 3x + -5x = -2x
(-15 + -2x + x2) = (x + 3) * x(x + 3)

Reorder the terms:
-15 + -2x + x2 = (3 + x) * x(x + 3)

Reorder the terms:
-15 + -2x + x2 = (3 + x) * x(3 + x)

Reorder the terms for easier multiplication:
-15 + -2x + x2 = x(3 + x)(3 + x)

Multiply (3 + x) * (3 + x)
-15 + -2x + x2 = x(3(3 + x) + x(3 + x))
-15 + -2x + x2 = x((3 * 3 + x * 3) + x(3 + x))
-15 + -2x + x2 = x((9 + 3x) + x(3 + x))
-15 + -2x + x2 = x(9 + 3x + (3 * x + x * x))
-15 + -2x + x2 = x(9 + 3x + (3x + x2))

Combine like terms: 3x + 3x = 6x
-15 + -2x + x2 = x(9 + 6x + x2)
-15 + -2x + x2 = (9 * x + 6x * x + x2 * x)
-15 + -2x + x2 = (9x + 6x2 + x3)

Solving
-15 + -2x + x2 = 9x + 6x2 + x3

Solving for variable 'x'.

Reorder the terms:
-15 + -2x + -9x + x2 + -6x2 + -1x3 = 9x + 6x2 + x3 + -9x + -6x2 + -1x3

Combine like terms: -2x + -9x = -11x
-15 + -11x + x2 + -6x2 + -1x3 = 9x + 6x2 + x3 + -9x + -6x2 + -1x3

Combine like terms: x2 + -6x2 = -5x2
-15 + -11x + -5x2 + -1x3 = 9x + 6x2 + x3 + -9x + -6x2 + -1x3

Reorder the terms:
-15 + -11x + -5x2 + -1x3 = 9x + -9x + 6x2 + -6x2 + x3 + -1x3

Combine like terms: 9x + -9x = 0
-15 + -11x + -5x2 + -1x3 = 0 + 6x2 + -6x2 + x3 + -1x3
-15 + -11x + -5x2 + -1x3 = 6x2 + -6x2 + x3 + -1x3

Combine like terms: 6x2 + -6x2 = 0
-15 + -11x + -5x2 + -1x3 = 0 + x3 + -1x3
-15 + -11x + -5x2 + -1x3 = x3 + -1x3

Combine like terms: x3 + -1x3 = 0
-15 + -11x + -5x2 + -1x3 = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(15 + 11x + 5x2 + x3) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(15 + 11x + 5x2 + x3)' equal to zero and attempt to solve: Simplifying 15 + 11x + 5x2 + x3 = 0 Solving 15 + 11x + 5x2 + x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 0.4a+0.7(13-a)=7.6 | | 9=-9b+2b | | 2x-35=2x+9 | | 9n-36=-18 | | 4(x-3)=12(x-5) | | p-9=-6p-3 | | 2x+20+4x-10=180 | | 3(x+4)-4=3(x-4) | | 0.25y=12 | | 3(x-4)-4=3(x-4) | | lnx=22.87 | | 2.5(fk+2)=12k | | 4x+3x=182 | | y^6-3y^4-y^3+3y^2-1=0 | | -6(6x-1)=-36x-6 | | 144x^2-1/4=0 | | y-9=-1(x-16) | | 50-2x=15+3x | | 14(v+4)-2v=3(4v+4)-18 | | y-9=-0.66(x-16) | | y-9=-(2)/(3)(x-16) | | y-9=-2/3(x-16) | | 3x-208=x/9 | | 5(x+7)=-30(x+2) | | -5(x+4)+3x+5=5x+12 | | -7(x+3)+3x+7=5x+11 | | ((d-4)/(4))^(2)=64 | | 1/3*6h=20 | | -3(2x+5)=7x+1 | | 7(x-7)+2=9-(x+6) | | 3(x-3)=2-8x | | x-3=.75(2-x)+6 |

Equations solver categories